1997
DOI: 10.1002/(sici)1097-4687(199704)232:1<57::aid-jmor3>3.3.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Hypochord, an enigmatic embryonic structure: Study of the axolotl embryo

Abstract: The hypochord of the axolotl embryo is first visible at an early tailbud stage, forming a rod-like structure, situated immediately under the notochord. A profusion of extracellular matrix fibrils is attached to the dorsolateral regions of the hypochord, linking it with the somites. A basal lamina develops around the hypochord, indicating an epithelial type of cell differentiation. Abundant rough endoplasmic reticula in the hypochord cells suggest lively synthetic activity. Prospective endoderm cells were vital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…3 for depiction of urostyle development in Hymenochirus boettgeri ). A comparable structure to the hypochord has also been found in lancelets, lampreys, fishes and urodeles, but is curiously absent from amniotes, suggesting secondary loss (see Löfberg & Collazo, 1997 and references cited therein). The embryonic (non‐ossified) hypochord has been implicated in regulating the medial migration of angioblasts to form the dorsal aorta in vertebrates (Cleaver & Krieg, 1998).…”
Section: How To Lose Vertebrae: Fusion and Preclusionmentioning
confidence: 70%
“…3 for depiction of urostyle development in Hymenochirus boettgeri ). A comparable structure to the hypochord has also been found in lancelets, lampreys, fishes and urodeles, but is curiously absent from amniotes, suggesting secondary loss (see Löfberg & Collazo, 1997 and references cited therein). The embryonic (non‐ossified) hypochord has been implicated in regulating the medial migration of angioblasts to form the dorsal aorta in vertebrates (Cleaver & Krieg, 1998).…”
Section: How To Lose Vertebrae: Fusion and Preclusionmentioning
confidence: 70%
“…The hypochord was believed to be a structure of mesodermal origin until 1997, when Lofberg and Collazo showed its endodermal origin by injection of vital dyes in axolotl embryos; the same authors have suggested that the hypochord might play a role in positioning the dorsal aorta (Lofberg and Collazo, 1997). Little is known about molecular markers of this structure in either model system: among the genes expressed in the zebrafish hypochord are some of the forkheadrelated genes (Odenthal and Nusslein-Volhard, 1998); in C. intestinalis, expression of Ci-fkh has been reported in trunk endoderm and endodermal strand (Di Gregorio et al, 2001).…”
Section: Endodermmentioning
confidence: 99%
“…The mesodermal or endodermal origin of the hypochord has been a matter of debate, but a consensus view between disparate anamniote species (including Xenopus laevis, axolotl and zebrafish) has emerged ascribing an endodermal character to this tissue (Cleaver et al, 2000;Eriksson and Lofberg, 2000;Lofberg and Collazo, 1997). Amniotes lack a hypochord but its function in patterning blood vessels may have been taken over by dorsal gut endoderm.…”
Section: Introductionmentioning
confidence: 99%